1994
DOI: 10.1073/pnas.91.21.10089
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and inducible nitric oxide synthase gene expression, regulation, and activity in human lung epithelial cells.

Abstract: Histochemical activity and immunoreactivt of nitric oxide synthase (NOS, EC 1.14.13.39) have been recently demonstrated in human lung epithelium. However, the molecular nature of NOS and the regulation and function of the enzyme(s) in the airway is not known. A549 cells (human alveolar type I epithelium-like), BEAS 2B cells (transformed human bronchial epithelial cells), and primary cultures of human bronchial epithelial cells all exhibited constitutive NOS activity that was calcium dependent and inhibitable b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
332
4
7

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(365 citation statements)
references
References 50 publications
16
332
4
7
Order By: Relevance
“…This was anticipated for the constitutive isoforms bNOS and eNOS (Asano et al, 1994;Kobzik et al, 1993;Shaul et al, 1994;Steudel et al, 1999), although an entire profile of cellular localization of both isoforms in lung tissue has so far not been shown. A recent study reported eNOS expression in epithelial cells, endothelial cells, and VSMC in normal rat lung tissue, which corresponds well with the data presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This was anticipated for the constitutive isoforms bNOS and eNOS (Asano et al, 1994;Kobzik et al, 1993;Shaul et al, 1994;Steudel et al, 1999), although an entire profile of cellular localization of both isoforms in lung tissue has so far not been shown. A recent study reported eNOS expression in epithelial cells, endothelial cells, and VSMC in normal rat lung tissue, which corresponds well with the data presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant expression of TNF-a and iNOS may indicate that TNF-a might contribute to induction of NOS in human stomach cancer. The induction of NOS in several tumor cell lines by various exogenous cytokines and cytokines released from themselves has been reported [6,24].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous NO is produced in the lung by a family of NO synthases [9][10][11]. This NO is thought to be an important modulator of vascular tone and airway function in normal airways.…”
Section: Aamentioning
confidence: 99%
“…According to some authors, normal subjects do not develop measurable obstruction in response to airway cooling [1][2][3], whereas other authors claim that they respond by developing measurable obstruction when the stimulus is sufficiently great [4,5]. Under these conditions, the origin and mechanisms involved in the development of bronchial obstruction are still under debate [6][7][8].Endogenous NO is produced in the lung by a family of NO synthases [9][10][11]. This NO is thought to be an important modulator of vascular tone and airway function in normal airways.…”
mentioning
confidence: 99%